Long-term all-cause mortality among asymptomatic individuals with 80th percentile of coronary calcium score based on age and gender in the St. Francis Heart Study. Issue 7 (November 2021) - Chen, Lu Q.; Weber, Jonathan; Christian, Timothy; Guerci, Alan D.; Cao, J. Jane
Abstract : Objectives: High coronary artery calcium score (CAC) is a significant risk factor for cardiovascular morbidity and mortality. We investigated the long-term outcome of subjects with elevated CAC. Methods: We studied 1005 participants of The St. Francis Heart Study who were asymptomatic and apparently healthy and had CAC scores at 80th percentile or higher for age and gender. They were randomized to receive atorvastatin 20 mg daily or placebo for up to 5 years. We used an as-treated study design accounting for cross-overs at the end of the original trial. All-cause mortality risk was assessed using adjusted hazard ratios. Results: Mean age was 59 ± 6 years and 26% ( N  = 263) were female. After 17 ± 3 years follow-up 176 subjects died. High CAC at baseline was associated with increased mortality risk with adjusted hazard ratio for logarithmic transformed CAC at 1.33 and 95% confidence interval 1.06–1.68. The mortality risk associated with CAC was similar between the group with high-sensitivity CRP ≥2 and <2 mg/dL. Those with a family history of premature coronary artery disease exhibited a higher mortality risk in association with high CAC with an adjusted hazard ratio 1.51 (1.09, 2.09). Conclusion: Elevated CAC is an independent risk for long-term all-cause mortality. The screening of CAC score in addition to identifying conventional risk factors can differentiate asymptomatic individuals with and without increased long-term mortality risk.